Palladium Supported on 3D Graphene as an Active Catalyst for Alcohols Electrooxidation. Issue 12 (1st January 2015) - Serov, Alexey; Andersen, Nalin I.; Kabir, Sadia A.; Roy, Aaron; Asset, Tristan; Chatenet, Marian; Maillard, Frederic; Atanassov, Plamen
Abstract : In the present study, highly porous 3D-Graphene nanosheets (3D-GNS) were synthesized using the Sacrificial Support Method (SSM) and utilized as a support for palladium (Pd) nanoparticles. The Pd nanoparticles were deposited using the original Pd-precursor based Soft Alcohol Reduction Method (SARM) with different alcohols. The obtained materials were comprehensively characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), and scanning transmission electron microscopy (SEM). Chemically reduced Pd/3D-GNS catalysts were then studied for the electrochemical oxidation of ethanol and methanol in alkaline media. Our study shows that combination of SSM and SARM-EtOH fabrication process allowed obtaining materials with a smaller particle size distribution and a higher surface area (yielding better utilization of Pd), as well as the highest electrochemical activity and durability, with a peak current density of over 1100 A/gPd for ethanol electrooxidation.